1985
DOI: 10.1161/01.res.56.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for protecting ischemic myocardium: results of the NHLBI Cooperative Study. Comparison of unconscious and conscious dog models.

Abstract: The Animal Models for Protecting Ischemic Myocardium Study was undertaken for the purpose of developing reproducible animal models that could be used to assess interventions designed to limit infarct size. This paper describes the results obtained in an unconscious dog model and in a conscious dog model, developed in three participating laboratories. The unconscious dog model, involving reperfusion after 3 hours of ischemia in open-chest dogs, was intended to determine whether therapy followed by early reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
5
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(157 citation statements)
references
References 43 publications
8
143
5
1
Order By: Relevance
“…Thus, in experimental studies of myocardial infarction, measurement of the area at risk is often presented as a necessary control for each animal [32], with the infarct size being normalized and expressed as a percentage of the area at risk. Because of large inter-animal variation in infarct size in canine models, the normalization to area at risk appears reasonable in this species [33]. In humans, while the size of the occluded coronary vascular bed is a determinant of infarct size, the difficulty of measuring the size of the riskzone in humans [34] precludes defining or normalizing clinical infarct size as a percentage of the area at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in experimental studies of myocardial infarction, measurement of the area at risk is often presented as a necessary control for each animal [32], with the infarct size being normalized and expressed as a percentage of the area at risk. Because of large inter-animal variation in infarct size in canine models, the normalization to area at risk appears reasonable in this species [33]. In humans, while the size of the occluded coronary vascular bed is a determinant of infarct size, the difficulty of measuring the size of the riskzone in humans [34] precludes defining or normalizing clinical infarct size as a percentage of the area at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in order to assess regional myocardial blood flow and infarct size, we followed the recommendations of the NHLBI cooperative study (Reimer et al, 1985 'O'Ru or "4"Ce (New England Nuclear, Boston, Massachusetts, U.S.A.), were injected through the catheter into the left atrial appendage, followed by a 10 ml saline flush. Beginning just before and continuing for 60 s after injection, a reference sample of arterial blood was withdrawn from the femoral artery at a rate of 9 ml min-'.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of measurements of myocardial blood flow in many of these studies has been suggested as a possible reason for the contradictory results reported in the literature (Reimer et al, 1989) since there could be differences in the level of collateral blood flow in control and treated groups. This was not considered to be a problem in our study since rabbits have been shown to have negligible coronary collateral blood flow (Maxwell et al, 1987 protection was reported with anti-neutrophil interventions were characterized by a shorter duration of coronary artery occlusion (Litt et al, 1989;de Lorgeril et al, 1989;Simpson et al, 1990), compared with most of those reporting no effect (Reimer et al, 1985;Chatelain et al, 1987). Furthermore, Jolly et al (1986) have previously reported that protection with anti-neutrophil antiserum in a canine model of acute myocardial infarction was lost when the duration of ischaemia was extended from 90 min to 4 h. Thus, there appears to be a difference between dogs and rabbits regarding the duration of ischaemia which can be tolerated.…”
Section: Discussionmentioning
confidence: 80%